2023
DOI: 10.1245/s10434-023-13188-x
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Excision of Soft Tissue Sarcomas of the Extremities in a Low-to-Middle-Income Country

Abstract: Background Outcomes of unplanned excisions of extremity soft tissue sarcomas (STSE) range from poor to even superior compared with planned excisions in developed countries. However, little is known regarding outcomes in low-to-middle-income countries. This study aimed to determine whether definitively treated STSE patients with a previous unplanned excision have poorer oncologic outcomes compared with those with planned excisions. Patients and Methods Using the database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The most frequently encountered histology differed across the literature; locally, high-grade liposarcomas The 148 ESTS patients included in Wang et al's study of unplanned excisions without metastasis on presentation were fairly distributed between low-(40%) and highgrade (60%) lesions. 8 In this study of F-ESTS patients, the majority (85%) were high-grade lesions. Comparing the outcomes of this study with Wang et al, there was a slightly higher local recurrence (25% vs 23%), almost double the rate of distant metastasis (65% vs 36%), and nearly half the survival rate (35% vs 63%).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The most frequently encountered histology differed across the literature; locally, high-grade liposarcomas The 148 ESTS patients included in Wang et al's study of unplanned excisions without metastasis on presentation were fairly distributed between low-(40%) and highgrade (60%) lesions. 8 In this study of F-ESTS patients, the majority (85%) were high-grade lesions. Comparing the outcomes of this study with Wang et al, there was a slightly higher local recurrence (25% vs 23%), almost double the rate of distant metastasis (65% vs 36%), and nearly half the survival rate (35% vs 63%).…”
Section: Discussionmentioning
confidence: 60%
“…Published data of non-metastatic ESTS cases in the same sarcoma unit would show an aggregate amputation rate of 12.8%. 8 The amputation rate of our F-ESTS study (40%) was much higher, considering the overwhelmingly high-grade nature of this group. Tumor size did not seem to be a factor in amputation since the size of F-ESTS was no different than the average size of STS presenting at the sarcoma unit (~11 cm).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Nonetheless, one must be aware that re-resections entail a higher risk of necessitating flap coverage or skin grafting when compared to primary resections [12,16,24]. This risk is particularly elevated in tumors of the distal extremities, including the hand and foot [25].…”
Section: Discussionmentioning
confidence: 99%
“…In cases with UE, Giuliano et al recommended definitive treatment with reoperation, either with or without radiotherapy. Recent studies have reported worse outcomes in patients with STS and a history of UE [8][9][10]. Consequently, the current standard of care for individuals who have undergone UE involves tumor bed excision with or without neo-adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%